Design of google site-based learning media for circle material to support critical thinking skills - Istiqomarie, Nurul; Hapizah, Hapizah; Mulyono, Budi (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
Background: Critical thinking ability is one of the 21st-century skills that are essential to solve problems related to contextual issues in everyday life. The rapid development of technology in the 21st century can be utilized by educators to innovate in response to learning needs, especially in the field of mathematics, which is often associated with everyday life. Aim: The purpose of this study is to design a valid and practical Google Site-based learning media for circle material in eighth grade that supports students' critical thinking skills.Method: This research employs a design and research (R&D) methodology with the ADDIE research procedure, consisting of the stages of analysis, design, development, implementation, and evaluation. The study was conducted in one of the junior high schools in Palembang city. Data collection techniques used were interviews, questionnaires, and tests, while data analysis techniques were quantitative and descriptive qualitative.Result: This study produced a Google Site-based learning media to support students' critical thinking abilities for circle material, which is valid, practical, and can enhance students' critical thinking skills based on the aspects of critical thinking stages according to Facione.Conclusion: The designed learning media can be an alternative for teaching circle material for junior high school teachers.